2016
DOI: 10.1016/j.jclinane.2016.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of the feasibility of three anesthetic techniques for day-case open inguinal hernia repair

Abstract: Study objective: Comparison of local anesthetic infiltration (LAI), spinal anesthesia (SPIN) and total intravenous anesthesia (TIVA) for open inguinal herniorrhaphy. We hypothesized that patients receiving LAI could be discharged faster than SPIN and TIVA patients. Design: Randomized, prospective trial. Setting: University hospital day-surgery center. Patients: 156 adult male patients (ASA 1-3) undergoing day-case open inguinal herniorrhaphy. Interventions: Patients were randomized to either LAI (lidocaine + r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Overall, 16 studies compared urinary retention after different types of anaesthesia. Four found a significantly lower incidence of urinary retention after LA compared with regional anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 16 studies compared urinary retention after different types of anaesthesia. Four found a significantly lower incidence of urinary retention after LA compared with regional anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs and three observational studies with no urinary retention recorded in any of the intervention groups were excluded from the meta‐analyses. No study was excluded based on the bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“… 38 This finding is similar to previous reports that demonstrated that local anesthetics lowered postoperative analgesic requirements compared with general anesthesia. 207 209 Compared with TAP block or caudal block, ilioinguinal/iliohypogastric nerve blocks did not provide substantial pain relief or reduce opioid consumption in the early postoperative period. 34 However, the use of ilioinguinal/ iliohypogastric nerve blocks for unilateral orchiopexy procedures provides short-term pain relief, and patients experience fewer side effects than with intravenous analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…Six RCTs and five cohort studies were included [3,[8][9][10][11][12][13][14][15][16][17]. A total of 2593 patients were recruited into this analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%